A consolidated method for screening the endocrine activity of drinking water. (15th December 2016) - Chevolleau, Sylvie; Debrauwer, Laurent; Stroheker, Thomas; Viglino, Liza; Mourahib, Issam; Meireles, Maria-Helena; Grimaldi, Marina; Balaguer, Patrick; di Gioia, Lodovico
Highlights: Concentration of 10 L drinking water samples with global concentration factor of 5000. SPE device exclusively made of material avoiding any plastic material contamination. Radiolabeled compounds used to track losses all along the concentration process. Abstract: Endocrine activity of drinking water is a matter of growing interest for scientists as well as health authorities. A concentration technique for endocrine activity screening was developed, optimized, and transposed from 200 mL to 10 L water samples. To avoid any contamination during concentration, the method was developed using exclusively glass, Teflon and stainless steel materials. Any potential losses were tracked using three model radiolabeled molecules, namely BPA, DEHP and 4n-NP. The final method allowed 10 L water samples to be concentrated 5000-fold, with good recovery and repeatability. After validation, by concentrating spiked and non-spiked 10 L samples of EVIAN natural mineral water, 14 different drinking water samples were concentrated and screened for endocrine disrupting activity using bioluminescent assays. Samples consisting of bottled water, conditioned in various materials (glass, PET) and subjected to different storage conditions, had no hormone-like activities whereas estrogenic activity was found in the filtered tap water.